Impact of Self Help Groups’Trainings on Empowerment of Rural Women of Udaipur District (Indian Journal of Extension Education, 2017)
Training and Development function plays a significant role in energizing and empowering human resources by increasing their skills through innovative and productive programmes. Women self-help groups are at present playing a vital role in the personality and skill development of women in India. The Institute of Local Self Government and Responsible Citizenship (ILSGRC),Vidya Bhawan Society, Udaipur has been conducting a two-day training program for SHG members for better functioning of SHGs at the local level. The training covered the information about SHGs, bank linkages, grading, government schemes and laws, health issues, participation in political process through Gram Sabha and Ward Sabha etc. The Institute has organized trainings for SHGs for the past six years but to date, impact of training was not assessed. Therefore, the present study was undertaken to study the effectiveness of training programmes. The present study was conducted in 2 Blocks namely Badgoan and Gogunda of the Udaipur District. Atotal eight SHGs were selected from 8 villages for the study. The sample consisted of 80 rural women SHG members. The results of the study demonstrate that women gained knowledge about proper functioning of SHGs, initiation of micro enterprises and laws and schemes of the women. The findings further show that their access was increased to the local level institutions like Anganwadi, Panchayat, schools, post office etc. which enhanced their access to health and education. Women had more decision making power in their household due to their SHG group and training. Thus the SHG training had been effective in empowering the SHG members.